A Theory of Debt Maturity and Innovation - Yuliyan Mitkov (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
I propose a theory of debt maturity as an incentive device to motivate innovation when contracts are fundamentally incomplete and shaped by ex-post renegotiation. The financing of innovative firms must balance two goals. On the one hand, since innovation is inherently risky, the entrepreneur must receive adequate protection after failure. Simultaneously, the firm must be liquidated when its assets can be redeployed more efficiently elsewhere. Meeting these two goals can be especially challenging when contracts are incomplete. I show how an appropriate choice of debt maturity, together with ex-post contract renegotiation, embeds a "put option" into the firm's capital structure. The put is exercised when liquidation is efficient, and it partially insures the entrepreneur against failure and thus motivates innovation. The theory has novel empirical implications for the financing patterns of innovative firms.
Keywords: C78; D82; D86; G32; G33; O31; O32; 330; Innovation; Debt maturity; Incomplete contracts; Renegotiation